An EFL student case study of English as a foreign language – TEFL program portfolio - Flores Torres, Mónica Cristina (2012)
Maestría en enseñanza del Inglés como lengua extranjera. Director: Pinza Tapia, Eliana Ivanova. Nota: ING. 125, CD. Modalidad: Abierta. ¼This thesis is the result of the professional experience achieved through the program with a real Student Case Study Portfolio and a professional analysis of the program according to The Teachers of English to Speakers of Other Languages (TESOL/NCATE) Standards.The thesis is divided in two sections that will take the reader to understand and analyze two areas of Teaching English as a Foreign Language. First chapter makes reference to a student case study as an extra-class writing tutorial that helps a high intermediate English language level student to solve her school writing difficulty. The student is almost at the end of the year and is concerned about her performance in writing, she is not achieving the goals of the program and she needs extra-class assistance in writing. On the other hand, second chapter focuses on a TEFL program portfolio that explains the NCATE/TESOL standards based on artifacts developed during this Masters Program.